2018
DOI: 10.3390/land7010024
|View full text |Cite
|
Sign up to set email alerts
|

“Medium-Scale” Forestland Grabbing in the Southwestern Highlands of Ethiopia: Impacts on Local Livelihoods and Forest Conservation

Abstract: Abstract:Tropical forest provides a crucial portion of sustenance in many rural communities, although it is increasingly under pressure from appropriations of various scales. This study investigated the impacts of medium-scale forestland grabbing on local livelihoods and forest conservation in the southwestern highlands of Ethiopia. Data were generated through interviews, discussions and document review. The results indicate that state transfer of part of the forestland since the late 1990s to investors for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 66 publications
(82 reference statements)
0
22
0
Order By: Relevance
“…This is most obvious in the mining green gold scenario, where poor land tenure rights, prioritization of national revenues, and the influence of external agricultural investors leads to a type of land grabbing, which would largely exclude local people from the financial benefits of development. Such development has been reported for other parts of Ethiopia where land grabbing by private agricultural investors has led to a displacement of smallholders from their farmland (Rahmato 2011), and, to a limited extent, in Jimma Zone (Ango 2018).…”
Section: Social-ecological Dynamicsmentioning
confidence: 61%
“…This is most obvious in the mining green gold scenario, where poor land tenure rights, prioritization of national revenues, and the influence of external agricultural investors leads to a type of land grabbing, which would largely exclude local people from the financial benefits of development. Such development has been reported for other parts of Ethiopia where land grabbing by private agricultural investors has led to a displacement of smallholders from their farmland (Rahmato 2011), and, to a limited extent, in Jimma Zone (Ango 2018).…”
Section: Social-ecological Dynamicsmentioning
confidence: 61%
“…Detailed recommendations on the complex and contentious issue of land scarcity are beyond the scope of this paper. At a basic level, however, and in view of land-grabbing in various parts of Ethiopia (Ango 2018 ), opening space for debate at the policy level, and exploring options for land sufficiency at the household level should at least be taken up; possibly alongside culturally appropriate efforts to address population growth. In relation to land access, sharecropping arrangements emerged to be an important means of accessing land in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…The largescale acquisition of agricultural land is practised by countries or private investors who are economically rich, but relatively limited in natural resources, with the aim of securing their food and energy supply for the future and ensuring large-scale control of land holdings beyond national borders (BORRAS JR & Franco, 2012). In the case studies we reviewed, land grabbing was identified as the reason for land-use change, for instance, in the south-western Highlands of Ethiopia and Sudan (Ango, 2018;Sulieman, 2015). More specifically, large-scale farmers played a role in 25% of all cases reviewed, and multinationals in 19%.…”
Section: Agricultural Development On Communal Landsmentioning
confidence: 99%